Prevalensi Atrioventrikular Blok di RSUP Prof. Dr. R. D. Kandou Manado Periode 2013 – 2014 - Wambrauw, Jery; Jim, Edmond L.; Joseph, Victor F. F. (Universitas Sam Ratulangi, 2017)
Abstract: AV Block conduction is an abnormality in which the impulse from the atrium has a delayed conduction or no conduction at all to the ventricle. This abnormality is classified as AV Block first degree, second degree, and third degree, depending on the severity of the abnormality. This was a descriptive retrospective study using second data as the reference. This study was aimed to obtain the prevalence of atrioventricular block at Cardiology Clinic Prof. Dr. R. D. Kandou Hospital Manado during 2013 – 2014. The results showed that of 40 patients, the highest percentage of cases had third degree AV block (21 patients; 53%), age group of 70-79 years (33%). Based on gender, there was the same number of cases of males and females, but the classification based on the degree of AV block showed that there were more male patients diagnosed as AV block first degree while there were more female patients diagnosed as third degree AV block. Hypertension was commonly found in the patients diagnosed as AV block as many as 18 patients (27%). Based on the chief complaint, most had difficulty of breathing (28%). However, each degree of the AV block had varied chief complaints and different kind of therapy. Based on the management, 77% of the patients had medical therapy with different kinds of medication.Keywords: AV block Abstrak: Blok konduksi AV merupakan kelainan yang mana impuls dari atrium dikonduksikan terlambat atau bahkan tidak dikonduksikan sama sekali ke ventrikel. Kelainan ini diklasifikasikan sebagai blok AV derajat satu, dua, dan tiga, tergantung pada keparahan abnormalitasnya. Penelitian dan bertujuan untuk mengetahui prevalensi blokade atrio-ventrikular di poli jantung RSUP Prof. Dr. R. D. Kandou Manado selama selang waktu 2013 – 2014. Jenis penelitian ialah deskriptif retrospektif menggunakan data sekunder sebagai acuan. Hasil penelitian mendapatkan dari 40 pasien, terbanyak ditemukan ialah AV blok derajat III (21 pasien; 53%); kelompok usia 70-79 tahun (33%). Berdasarkan jenis kelamin didapatkan jumlah yang sama antara pasien laki-laki dan perempuan, namun dalam pembagian berdasarkan derajat AV blok didapatkan pasien laki-laki lebih banyak dengan diagnosis AV blok derajat I sedangkan perempuan lebih banyak pada AV blok derajat III. Penyakit penyerta terbanyak ditemukan ialah hipertensi (18 pasien; 27%). Berdasarkan keluhan penyerta pada pasien AV blok terbanyak ditemukan ialah sesak nafas (28%) namun untuk masing-masing derajat AV blok keluhan yang paling sering dialami berbeda-beda, dan berdasarkan penatalaksanaan yang diberikan 77% pasien di terapi dengan obat-obatan.Kata kunci: AV blok